Representasi Sikap dan Filsafat Hidup Pengarang dalam Novel Surga yang Tak Dirindukan Karya Asma Nadia - Muyassaroh; Muntik Latifatunnadhiroh; Galuh Ayu Larassati; Laiyin Farikha (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study analyzes Asma Nadia’s attitudes and worldview regarding the issues of marriage and polygamy as depicted in the novel Surga yang Tak Dirindukan (The Heaven That Is Not Longed For). The research is motivated by the thematic relevance of the novel to the social realities faced by women and the dynamics of gender relations in modern society. A qualitative descriptive approach is employed, utilizing literary text analysis as the method, while the data are collected through critical reading and systematic note-taking. The findings reveal that the author perceives marriage as an institution ideally grounded in loyalty, justice, and sacrifice. Through character development, Asma Nadia portrays the inner conflicts and emotional struggles experienced by women confronted with the practice of polygamy. Her empathetic and humanistic stance is reflected in the narrative, which emphasizes the perseverance and resilience of female characters. In conclusion, the novel serves as a medium of social criticism against unjust polygamy practices and advocates for the values of justice and humanity within the family institution.